Ischemic Stroke in an HIV Positive Patient: An Initial Presentation of Neurosyphilis - Kalimullah Jan; Rebecca Hoe Hui Min; Tan Seow Yen; Shekhawat Ravindra Singh (Case Reports in Neurological Medicine)
Ischemic stroke occurring in patients with human immunodeficiency virus (HIV) needs to be approached with a vast differential diagnosis in mind. We report a case of middle-aged male patient with immune reconstituted HIV on therapy without known cardiovascular risk factors who had a right middle cerebral artery territory infarct. After a thorough evaluation, he received a final diagnosis of neurosyphilis-associated vasculitis leading to stroke. He recovered without any neurological deficits following treatment with intravenous benzylpenicillin. Neurosyphilis is an easily diagnosed and treatable cause of a stroke that can be an initial presentation of neurosyphilis but requires a high index of suspicion.